Risk factors with the development of infection with tigecycline- and carbapenem-resistant Enterobacter cloacae - Jiang, Yuansu (Infect Drug Resist, 2019)
BACKGROUND: Tigecycline is regarded as a last resort treatment for carbapenem-resistant Enterobacter cloacae (CREC) infections, and increasing numbers of tigecycline- and carbapenem-resistant E. cloacae (TCREC) isolates have been reported in recent years. However, risk factors and clinical impacts of these isolates are poorly characterized. PATIENTS AND METHODS: We conducted a retrospective case-case-control study of hospitalized patients with TCREC infection during the period 2012–2016 in Chongqing, China. Case patients with TCREC and those with CREC were compared to a control group with no E. cloacae infection. Multivariate logistic regression models were used to identify independent risk factors for acquiring TCREC and CREC. RESULTS: A total of 36 TCREC cases, 36 CREC cases, and 100 controls were enrolled in our study. Multivariable analysis indicated that nasal catheter (OR: 8.9; 95% CI: 1.1–75.2), exposure to penicillin (OR: 95.9; 95% CI: 8.9–1038.3), aminoglycosides (OR: 42.1; 95% CI: 2.1–830.6), and fluoroquinolones (OR: 18.6; 95% CI: 1.9–185.6) were independent predictors for acquiring TCREC. In addition, venous catheterization (OR: 12.2; 95% CI: 2.5–58.5), penicillin (OR: 30.8; 95% CI: 7.9–120.0), and broad-spectrum cephalosporin (OR: 5.0; 95% CI: 1.5–17.3) were independently associated with CREC acquisition. CONCLUSION: Reasonable antibiotic stewardship programs and surveillance are necessary to control the tigecycline resistance among high-risk patients.